Rationale and Application of PEGylated Lipid-Based System for Advanced Target Delivery of siRNA - Ge, Xuemei; Chen, Lijuan; Zhao, Bo; Yuan, Weien (Frontiers in Pharmacology, 2021)
RNA interference (RNAi) technology has become a powerful tool in application of unraveling the mechanism of disease and may hold the potential to be developed for clinical uses. These antisense oligonucleotides can bind to target mRNA with high specificity and efficacy and thus inhibit the expression of related protein for the purpose of treatment of diseases. The major challenge for RNAi application is how to improve its stability, and bioactivity and therefore deliver therapeutic agents to the target sites with high efficiency and accuracy. PEGylated lipid based delivery system has been widely used for development of various medicines due to its long circulating half life time, low toxicity, biocompatibility and easiness to be scaled up. The PEGylated lipid based delivery system may also provide platform for targeting delivery of nucleic acids, and some of the research works have move to the phases for clinical trials. In this review, we introduced the mechanism, major challenges, strategies to overcome technical barriers of PEGylated lipid based delivery systems for advanced target delivery of siRNA in vivo. We also summarized recent advance of PEGylated lipid based siRNA delivery systems and included some successful research work in this field.